1979
DOI: 10.1111/j.1348-0421.1979.tb00451.x
|View full text |Cite
|
Sign up to set email alerts
|

UV Survival of Human Mycoplasmas: Evidence of Dark Reactivation in Mycoplasma buccale

Abstract: The inactivation by ultraviolet (UV) light irradiation of mycoplasma cells of five human strains was monitored by investigating the colony-forming ability. The survival curves of five strains tested indicated that the cells of Mycoplasma buccale only are single and homogenously susceptible to UV light. The effect of the repair inhibitor, caffeine, on the colony-forming ability of UV-irradiated cells was investigated with Al. buccale because of its homogenous susceptibility to UV light. The colony formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0
1

Year Published

1982
1982
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 37 publications
0
8
0
1
Order By: Relevance
“…It has been suggested that variations in the amounts and/or activities of enzymes involved with DNA repair could cause the biased mutation pressure in these organisms (33,47). However, there have been few studies on DNA repair processes and the enzymes involved with such processes in these organisms (1,12,18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that variations in the amounts and/or activities of enzymes involved with DNA repair could cause the biased mutation pressure in these organisms (33,47). However, there have been few studies on DNA repair processes and the enzymes involved with such processes in these organisms (1,12,18).…”
mentioning
confidence: 99%
“…Inhibitor activity was determined in both a HEPES (N-2-hydroxyethylpiperazine-N'-2-ethanesulfonic acid)-buffered system (HEP) and a Tris-buffered system (TRI). The HEP system contained the following in a total volume of 0.2 ml: 70 mM HEPES-KOH (pH 7.8), 1 (Fig. 1B) ULT uracil residues ( Fig.…”
mentioning
confidence: 99%
“…laidlawii (Ghosh et al, 1978). It should be noted that Aoki et al (1979) were unable to detect a dark repair system in M. buccale and Ghosh et al (1977) failed to observe both photoreactivation and dark repair in M. gallisepticum. This last point raises questions about how an organism that appears to lack these critical repair systems is able to maintain fidelity in the replication of its genome.…”
Section: Dna Repair and Recombinationmentioning
confidence: 89%
“…Survival curves versus UV exposure typically show a shoulder near the origin followed by logarithmic killing (Aoki et al, 1979;Maniloff and Morowitz, 1972). Dark repair and photoreactivation have been demonstrated in A. laidlawii (Das et al, 1972).…”
Section: Dna Repair and Recombinationmentioning
confidence: 99%
“…The mycoplasmas arc exceedingly sensitive to ultraviolet (UV) and gamma radiation . Survival curves versus UV exposure typically show a shoulder near the origin followed by logarithmic killing (Aoki et al, 1979;Maniloff and Morowitz, 1972). Dark repair and photoreactivation have been demonstrated in A. laidlawii (Das et al, 1972).…”
Section: Dna Repair and Recombinationmentioning
confidence: 99%